2020
DOI: 10.1126/sciadv.aaz7070
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 derived from endometrial extracellular vesicles is an important inducer of embryonic diapause in mice

Abstract: Embryonic diapause is a maternally controlled phenomenon. The molecule controlling the onset of the phenomenon is unknown. We demonstrated that overexpression of microRNA let-7a or incubation with let-7g–enriched extracellular vesicles from endometrial epithelial cells prolonged the in vitro survival of mouse blastocysts, which developed into live pups after having been transferred to foster mothers. Similar to in vivo dormant blastocysts, let-7–induced dormant blastocysts exhibited low level of proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…For example, endometrial epithelial cell-derived exosomes promote embryo attachment during implantation via miR-30d-dependent upregulation of integrins or through activation of focal adhesion kinase (FAK) signaling pathway ( 107 , 108 ). Another study shows that diapausing endometrial epithelial cell-derived exosomes enriched with miR-let-7 can protect the embryo from collapsing ( 109 ). Conversely, embryo-derived exosomes have been detected in spent embryo culture medium.…”
Section: Pexo As a Modulator Of Maternal Immune Tolerancementioning
confidence: 99%
“…For example, endometrial epithelial cell-derived exosomes promote embryo attachment during implantation via miR-30d-dependent upregulation of integrins or through activation of focal adhesion kinase (FAK) signaling pathway ( 107 , 108 ). Another study shows that diapausing endometrial epithelial cell-derived exosomes enriched with miR-let-7 can protect the embryo from collapsing ( 109 ). Conversely, embryo-derived exosomes have been detected in spent embryo culture medium.…”
Section: Pexo As a Modulator Of Maternal Immune Tolerancementioning
confidence: 99%
“…Let-7 is a major factor that induces diapause in embryos. Let-7-containing EVs from uterine fluid induce mouse embryonic diapause by inhibiting cmyc/mTORC1 and mTORC2 signaling pathways (73,74). Overexpression of EVs-derived let-7 potentially hamper trophoblast differentiation and the implantation capacity of embryo (73,74).…”
Section: Lethal-7 Familymentioning
confidence: 99%
“…Exit from diapause is triggered by an increase in uterine receptivity that either occurs when lactation ends or can be experimentally induced by injection of estradiol. Mouse blastocysts can also be induced to enter a diapause-like paused state ex vivo via a few alternate methods for variable durations, including chemical inhibition of the cytoplasmic kinase mTOR (up to 30 days after blastocyst formation) (Bulut-Karslioglu et al, 2016), inhibition of the transcriptional regulator Myc (18 h) (Scognamiglio et al, 2016), and overexpression of the microRNA let-7 (up to 14 days) (Liu et al, 2020). These molecular regulators are further discussed below.…”
Section: Triggers Of Diapause and Reactivationmentioning
confidence: 99%
“…Nonetheless, qualitative evidence can be obtained. Indeed, Liu et al (2020) recently showed a slight delay in the development of human blastocysts upon treatment with extracellular vesicles carrying the microRNA let-7g (52% vs. 30% day 7 survival in treated vs. control embryos). Human blastocysts were also reported to undergo diapause when coated with a mucin-mimicking synthetic gel, however, these did not retain the characteristic blastocyst morphology (Canton et al, 2016).…”
Section: The Possibility Of Diapause In Humansmentioning
confidence: 99%
See 1 more Smart Citation